Perturbation Theory and Dalgarno-Lewis (DL) Method in Presence of Multiple Laser Beams - Shrestha, N (Nepal Journal of Science and Technology, 2014)
The evaluation of second and higher order perturbation of energy by iterative solution of Schrodinger’s equation, rather than evaluation of matrix element is described. DOI: http://dx.doi.org/10.3126/njst.v14i2.10432 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 165-170